Mapping the regulatory space for genetic databases and biobanks in England and wales - Kaye, J; Gibbons, S (2008)
The 'regulatory space' metaphor articulated by Hancher and Moran offers a useful framing device for mapping and understanding the complex dynamics and patterns of interaction between the actors who populate existing regulatory regimes. This paper applies the 'regulatory space' analytical approach to map out and, thereby, gain a deeper understanding of, the current governance of genetic databases and biobanks in England and Wales. The paper draws on legal research undertaken for an ongoing socio-legal project into genetic database governance. It demonstrates some benefits of using the regulatory space approach as a precursor to applying normative theories and principles to formulate specific recommendations for regulatory reform. It also identifies potential pitfalls. The findings and conclusions should assist in designing policy recommendations for regulating genetic databases and biobanks better in the future. © 2008 A B Academic Publishers - Printed in Great Britain.